2012
DOI: 10.3945/jn.111.156398
|View full text |Cite
|
Sign up to set email alerts
|

Alkylresorcinol Metabolite Concentrations in Spot Urine Samples Correlated with Whole Grain and Cereal Fiber Intake but Showed Low to Modest Reproducibility over One to Three Years in U.S. Women

Abstract: Two alkylresorcinol (AR) metabolites, 3, 5-dihydroxybenzoic acid (DHBA) and 3-(3,5-dihydroxyphenyl)-1-propanoic acid (DHPPA), in urine have been suggested as biomarkers of whole grain (WG) and cereal fiber intake but the long-term reproducibility and correlation with habitual intake has not been determined. Therefore, we evaluated the long-term reproducibility of AR metabolites in spot urine samples and investigated their correlation with habitual WG and cereal fiber intake in U.S. women. AR metabolites were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…This is in line with a recent study showing low reliability in spot urine. 10 Higher AR metabolite concentrations observed for men versus women are probably due to higher intact AR concentrations in men, as observed previously among these participants. 4 This may partly be explained by higher intake of AR containing foods or by lower clearance of intact AR among men versus women.…”
Section: Resultssupporting
confidence: 64%
“…This is in line with a recent study showing low reliability in spot urine. 10 Higher AR metabolite concentrations observed for men versus women are probably due to higher intact AR concentrations in men, as observed previously among these participants. 4 This may partly be explained by higher intake of AR containing foods or by lower clearance of intact AR among men versus women.…”
Section: Resultssupporting
confidence: 64%
“…So far, no study has reported the presence of these novel metabolites in urine after rye consumption, and it is possible that the urinary AR metabolite composition differ after wheat and rye intake. This is supported by the DHPPA/DHBA ratio in urine which is usually >2 after wheat-based AR intake as reported here and elsewhere [9,25], while the ratio in studies where rye is the primary AR source commonly <2 after rye-based AR consumption [16,17,33,34]. Unlike previous studies [16,17], no inverse relationship between AR intake and urinary AR metabolite recovery was observed.…”
Section: Discussionsupporting
confidence: 54%
“…This suggests that 24-h urinary excretion of AR metabolites cannot only distinguish between WG wheat consumers and non-consumers but can also be used to differentiate between levels of WG wheat intake. Shorter collection intervals (e.g., spot urine samples) may reflect WG intake less effectively and be less reproducible than 24-h collections [17,25], although a WG serving (16 g of WG) increment increased 12-h DHPPA urinary excretion by 67 % based on a 12-h urine sample in a US population [26], against a background of very low overall WG intake.…”
Section: Discussionmentioning
confidence: 98%
“…Because major sources of AR, such as ready-to-eat cereal and whole-grain wheat bread, are usually consumed on a daily basis, plasma AR may be a useful marker of habitual consumption in populations with a stable intake of whole-grain foods. Al-though, urinary AR metabolites have been correlated with whole-grain intake in the US populations (14,15), data on the use of plasma AR as surrogate biomarkers of total whole-grain intake in both elderly and free-living adults in the United States are scarce. In northern European populations who consume predominantly whole-grain rye, plasma AR has been found to correlate with intake of whole grain (16,17).…”
Section: Introductionmentioning
confidence: 99%